PENERAPAN MODEL AKTIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PAI SISWA KELAS V SDN 04 TANJUANG HARO - Irmawanti Irmawanti; Zulfani Sesmiarni; Rodi; Masyitah Shellyni (CV. ADIBA ASIHA AMIRA, 2024)
Study Action Class This aiming For increase results Study Islamic Religious Education through application of the active learning model on student Class V at SDN 04 Tanjuang Haro . As for background behind study This is results Study part big student on eye PAI lessons show low yield or be under standard minimum competency . This is due to by low level involvement student in the learning process , as well domination method less lecture interesting interest Study students . Research This use PTK design implemented in four cycle , where every cycle consists of from stage planning results observation , implementation , observation , and reflection . Subject study is 14 students Class V of SDN 04 Tanjuang Haro . Data collected covering to activity learning And results assessment beginning And end . Results study show that the application of the active learning model can increase results students learning Islamic Religious Education class V of SDN 04 Tanjung Haro . On cycle I, average value student experience improvement compared to with Pre Cycle , namely about 50 % of students reach minimum completion . On cycle II, improvement results Study student around 71.43 % . At cycle III, improvement results Study student around 92.86 %. Apart from that , the result observation show that student more motivated And involved active in the learning process that uses the active learning model . With Thus , it can concluded that the active learning model is effective in increase results Study Islamic Religious Education in student Class V of SDN 04 Tanjuang Haro.